IJCM_193A: To study prevalence of hypertension among medical nursing staff at Maharashtra: A cross sectional study - Gopalrao Chopade Manda; Gattani P.L; Maidapawad S (Wolters Kluwer Medknow Publications, 2024)
Background: Hypertension, a leading public health concern worldwide, is a significant risk factor for cardiovascular diseases, which are the top cause of global mortality. In India, hypertension contributes substantially to noncommunicable disease burden. Healthcare professionals, particularly nurses, are expected to have lower prevalence due to their medical background. However, factors like high-stress work environments and demanding work conditions may increase their susceptibility to hypertension. This study aims to explore the prevalence of hypertension among nursing staff at Maharashtra, considering their unique occupational challenges. Objectives: To study prevalence of hypertension among Medical Nursing staff Methodology: This cross-sectional study was conducted at Government Medical College at Maharashtra, targeting the entire cohort of medical nursing staff over a period of three months. The study employed total enumeration sampling, including all medical nursing staff at the college. Data collection involved face-to-face interviews using a pretested and pre- validated questionnaire. Results: Prevalence of hypertension among nursing staff was 100 (21.96%). Most participants with HTN are in the 31-40 age range (55.6%), which is also the largest group without HTN (52.4%). Vegetarians are more likely to have HTN (60.2% vs. 43.8% in non-HTN), while the mixed diet group is more prevalent in the non-HTN group (56.2% vs. 39.8% in HTN) which have significant association(p=0.0078) Conclusion: The study highlights the prevalence of hypertension and its associated risk factors among nursing staff at Medical College at Maharashtra. The findings underscore the need for targeted health interventions and stress management strategies within this group, considering their critical role in healthcare delivery and their exposure to high-stress occupational environments.